Borax‐catalyzed valorization of waste rubber and polyethylene using pyrolysis and copyrolysis reactions. Issue 5 (9th August 2021) - Hussain, Zahid; Khan, Ajmal; Naz, Muhammad Yasin; Jan, Mohammad Rasul; Khan, Khalid Mohammed; Perveen, Shahnaz; Ullah, Sami; Shukrullah, Shazia
Abstract: Borax catalyst was used to pyrolyze and copyrolyze the waste polyethylene and tire tube rubber into combustible oil and gas. The borax catalyst not only acted as a solid base but also offered empty orbitals to cleavage the bonds of polymeric feedstock and secondary cracking reactions. The pyrolysis reactions were carried out in a custom‐made steel reactor placed in a top load furnace equipped with digital temperature controller. Both polymeric wastes were pyrolyzed separately and by combining in different ratios with and without using borax catalyst. The effect of reaction temperature and time on quality and quantity of liquid and gaseous products was investigated in the range of 200°C to 600°C and 15–75 min, respectively. In noncatalytic pyrolysis, the pure and copyrolyzed polyethylene with rubber yielded maximum oil at 500°C and 600°C, respectively. In borax‐catalyzed pyrolysis, the pure polyethylene and copyrolyzed with rubber yielded maximum oil at 400°C and 500°C, respectively. Notable difference in product fractions of conventionally pyrolyzed and borax‐catalyzed pyrolysis was evident at all process temperatures. The chemical nature of oil was checked using GC–MS, while gaseous product was analyzed using glass vessel traps containing different chemical reagents. The combustibility of gaseous product was also checked using a miniature Bunsen burner.